Analisis Penilaian Kinerja Keuangan Dengan Menggunakan Metode Economic Value Added Pada PT Sarimelati Kencana Tbk Di Bursa Efek Indonesia - Muliana Agus; Nurman Nurman; Anwar Ramli; Anwar Anwar; Hety Budiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the financial performance of PT. Sarimelati Kencana Tbk when measured using Economic Value Added. The population in this study is all financial report data of PT. Sarimelati Kencana Tbk, while the samples in this research are financial position reports and profit/loss reports. The data collection technique used is documentation techniques. The data collected is analyzed using Economic Value Added calculations. The results in this research show that the financial performance of PT. Sarimelati Kencana Tbk, if measured using Economic Value Added (EVA), produces a positive value, meaning that PT. Sarimelati Kencana Tbk is able to create added economic value. and said PT. Sarimelati Kencana Tbk has good performance.